THE TRADE OF THE RAICILLER - Gutiérrez, María Rosa Nuño; Ochoa, Angélica Navarro (Mercator, 2021)
The goal of this work is to analyze the production of raicilla, a distillate of agave, as a community value, one which mobilizes social actors who strive to maintain a role and a voice in society. They also seek the sustainable development of their environment and, consequently, the socio-economic progress of their families and communities. From a sociological perspective and using a qualitative methodology, the study assesses the representations and social imaginaries of the artisanal distillers who produce raicilla. It also allows an understanding of the problems and vicissitudes that they confront in order to maintain and conserve part of the cultural heritage of the west coast-mountain region of Jalisco. Keywords : Raicilla, Identity Regional, Local Development, Social Representations, West Coast-mountain Jalisco.